An industrial case study of implementing software risk management. - Freimut, Bernd (Software engineering notes.)
Explicit risk management is gaining ground in industrial software development projects. However, there are few empirical studies that investigate the transfer of explicit risk management into industry, the adequacy of the risk management approaches to the constraints of industrial contexts, or their cost-benefit. This paper presents results from a case study that introduced a systematic risk management method, namely the Riskit method, into a large German telecommunication company. The objective of the case study was (1) to analyze the usefulness and adequacy of the Riskit method and (2) to analyze the cost-benefit of the Riskit method in this industrial context. The results of (1) also aimed at improvement and customization of the Riskit method. Moreover, we compare our findings with results of previous case studies to obtain more generalized conclusions on the Riskit method. Our results showed that the Riskit method is practical, adds value to the project, and that its key concepts are understood and usable in practice. Additionally, many lessons learned are reported that are useful for the general audience who wants to transfer risk management into new projects.